PERBANDINGAN SISTEM PEMBAGIAN WARIS DALAM HUKUM INDONESIA DAN MALAYSIA - bero, Suripto; Fikri, Sariatul; Mujib, Mishbachul (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research focuses on examining more specifically the comparison of inheritance distribution systems in Indonesian and Malaysian law. Both are Muslim-majority countries that apply Islamic law in the distribution of inheritance, but each has different legal systems and policies in regulating inheritance. This research method is a type of qualitative research using the Library Research method. The research results show that Indonesia adopts a pluralistic legal system which includes Islamic law, customary law and civil law in the division of inheritance, while Malaysia implements a dualistic legal system with a separation between Sharia law for Muslims and civil law for non-Muslims. The similarities between the two countries lie in the basis of Sharia law which guides the distribution of Muslim inheritance, including the application of the faraid principle.